CUSTOMER REVIEWS AND INFLUENCER ENDORSEMENTS ON PURCHASE DECISIONS MEDIATED BY TRUST IN THE GOFOOD PLATFORM - Andri Aulia Lubis; Erwansyah (Fakultas Ekonomi Universitas IBA, 2025)
This study examines the influence of customer reviews and influencer endorsements on purchase decisions with trust in the GoFood platform as a mediating variable. Using a quantitative approach, the research collected data from 150 active GoFood users in Medan, Indonesia. Data were analyzed using Structural Equation Modeling (SEM-PLS) through SmartPLS software. The findings reveal that both customer reviews and influencer endorsements have a significant positive effect on purchase decisions directly and indirectly through platform trust. These results highlight the importance of strengthening consumer trust as a strategic factor to increase purchase intentions and customer loyalty in digital food delivery services.